PENGELOLAAN LAHAN PEKARANGAN/KEBUN DENGAN SENGON SOLOMON HASIL KULTUR IN VITRO PADA KELOMPOK USAHA PEMBIBITAN SENGON DI KABUPATEN MALANG - Kusmawati, Wiwik; Zaini, Moh.; Ernata, Yusvidha (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2018)
Sengon nursery business groups, especially in Poncokusumo Subdistrict and Wajak Subdistrict, Malang Regency still rely on sengon seeds that grow wild in nature with low growth rates. Though sengon seeds are a commodity of high economic value. This can be seen from the small number of breeders who manage the sengon seeds well. Even though the availability of plant seeds is a factor that plays a major role in the success of the sengon plant forest development program. Quality seeds with the support of aquaculture technology can provide high quality seeds so they can produce quality trees and wood products. The stages of implementing PKM activities are as follows: (a) Survey and planning, (b) Counseling and training